Crystal structure, optical properties, and theory study of a 1-D bromoplumbate stabilized by in situ generated N-alkylated DABCO cation. Issue 11 (3rd June 2017) - Tong, Hua-Nan; Lin, Jian-Di; Rong, Cheng; Li, Jing-Min; Wang, Yu-Lin; Guo, Guo-Cong; Lv, Ri-Xin
Abstract: We report the exploration of the stabilization effect of the in situ generated N -alkylated DABCO (DABCO = 1, 4-diazabicyclo[2.2.2]octane) cation in the family of bromoplumbates and a 1-D bromoplumbate, (Et2 DABCO)2n (Pb3 Br10 )n (1 ), has been prepared by solvothermal conditions. Optical diffuse reflectance determination shows the band gap of1 is 3.69 eV, which manifests that1 is a wide band gap semiconductor. Compared with the band gap of bulk PbBr2 (3.84 eV), 1 exhibits 0.15 eV red shift of absorption edge. While for the reported iodo analogs of this compound, (MPDA)2n (Pb3 I10 )n and (Et2 DABCO)2n (Pb3 I10 )n, they exhibit 0.53 and 0.47 eV blue shift of the energy gaps compared with the measured value of 2.30 eV for bulk PbI2, respectively. The photoluminescent study of1 shows that it exhibits a broad emission band centered at 697 nm upon photoexcitation by 345 nm (amount to 3.59 eV). The calculated density of states manifests the theoretical value of the band gap of1 is 3.422 eV and the origination of photoluminescence can be ascribed to the transition of bonding electrons of Br – anion to the empty orbits of Pb(II) ion. Abstract :